Emergence of a world made other : a study of the social teachings of François Houtart - Sahabandhu, Jerome (Irish School of Ecumenics, 2009)
Francois Houtart is a Belgian social activist and sociologist of religion who defends the position that religion, as a social reality, can be an agent of change in a given situation. Houtart's ideas originate from Weber, Marx and Gramsci; for Houtart, religion is a social construction. Throughout Houtart's career he has struggled for social justice, especially in subaltern societies, expressed through his forceful resistance to capitalist globalisation, encouragement for the convergence of social movements, and emphasis upon the importance of collective consciousness and praxis within the changing global context.
Keywords: Ecumenics, Ph.D.; Ph.D. Trinity College Dublin.